Job stress among offshore personnel in oil and gas extraction industries - Afzainizam, N. (Indian Society for Education and Environment, 2016)
Objective: This paper discusses about the job stress among offshore oil and gas extraction industry personnel and some possible suggested prevention to avoid it from getting worse. The physical and psychosocial aspects of the offshore oil work environment, job characteristics, job satisfaction, individual differences of mental and physical health will be given priority in this paper. Methods/Statistical Analysis: The cause of job stress among offshore personnel in the oil and gas extraction industries was studied based on the approach used in the offshore research which carried out in 1995 by Oxford University that include a total of 6 personnel. Findings: Overall, all personnel deal with stress yet they are facing it at different levels. Those with high post cope with stress better than their lower post mates. It is clear too that the offshore working community presents unique situations that need to be addressed specifically, rather than the routine of the normal people onshore. The study also reveals some unique features of the offshore workplace and a number of possible solutions to curb stress amongst those in industries. The process of developing solutions is often seen as the most difficult part of managing the possible causes of work-related stress. The ideal to aim for is the development of locally developed solutions that take into account the particular context of the workplace. Applications/Improvements: The results from this study showed that workers are stressed with no matter where they worked, and steps need to be taken in order to improve the productivity of the workers.